Young Children’s Ability to Integrate Social and Numerical Information: The Origins of Base-rate Neglect - Gualtieri, Samantha (University of Waterloo, 2019)
The seminal work of Kahneman and Tversky (1973) sparked an interest in the biases that govern decision-making, notably due to their findings on adults’ tendency to neglect base-rate information (i.e., prior probability) when it conflicts with social information (e.g., a personality description, or testimony information). Though research over the past 45 years uncovered the conditions that lead to base-rate neglect, very little has investigated the origins of these biases. Young children can use base-rate and social information on their own, but their ability to integrate this information remains poorly understood. Do children show a preference for social information as soon as they are able to use it? Or, does their preference for social information develop over time? The current thesis explores 4- to 6-year-old children’s ability to integrate base-rate and social information, providing insight into the origins of base-rate neglect. In three projects, I assessed young children’s ability to integrate base-rate and social information. A first project investigated children’s use of base-rate information when it conflicted with individuating information (i.e., a personality description). Typically, adults classify an individual by evaluating how well the individuating information matches a stereotypical member of each social group, underusing prior base-rates of the groups in their decision. Using stereotypes familiar to young children, I presented them with an 8:2 base-rate of characters (e.g., 8 nice, 2 mean). One character was randomly selected from the group, with its membership unknown, and children were given a short personality description. By age 6, children performed similarly to adults and over relied on individuating information. Notably, 4-year-olds preferred base-rates more than the older age groups. I further explored these age differences in a second project that manipulated the quality of the base-rate and individuating information given. Six-year-olds’ use of base-rates varied with manipulations depending on the strength of the available individuating information. However, 4-year-olds consistently used base-rates across manipulations, even in situations where it would be reasonable to rely on the individuating information. Thus, children seem to initially show a preference for base-rate information and develop a bias toward individuating information by the age of 6, though attempt to reconcile individuating information with base-rates. A third project extended my findings to another type of social information. I presented children with testimony information from a witness that conflicted with base-rates. Rather than integrating information, adults typically use the witness’ accuracy alone, thus neglecting base-rates. Here, 4- and 5-year-olds relied exclusively on an accurate witness, but they integrated information when the witness was less accurate. For young children, testimony from a witness is a strong cue, even stronger than stereotypical information. With findings from the youngest age group tested to date, my dissertation provides evidence that heuristic strategies strengthen with development and vary depending on the type of social information provided. These findings highlight the importance of research on the role of age-related changes in experience and cognitive abilities in information integration strategies.